'Working at becoming a communist': institutional belonging and political self-making of women in the Communist Party of India (Marxist). Issue 1 (2nd January 2023) - Raychaudhury, Proma
ABSTRACT: Gendered relations of power contribute to the signification inherent in political parties. The formal rules and informal processes through which hegemonic gender regimes are reproduced and contested in the Communist Party of India (Marxist) (CPI(M)) are subjected to Feminist Institutionalist analysis here. In addition, the institutional belonging and political self-making of women party members are also assessed in the state of West Bengal. The experiential concepts of institutional belonging and self-making can enhance Feminist institutionalist research by identifying the processes that shape gendered behaviour of actors in institutions. The idealised revolutionary communist subjectivity that represents the institutional standard of appropriateness of gendered behaviour in the CPI(M) is explored. The co-constitutive relationship between institutions and political subjectivities is elaborated. The paper argues that the institutional belonging and political self-making of women in the CPI(M) are characterised by a politics of boundary-creation from as well as horizontal solidarities with fellow women colleagues.